Proyecto de factibilidad de implementación de una empresa de servicios de agroturismo para la ciudad de Santo Domingo de los Colorados, en la provincia de Santo Domingo de los Tsáchilas - Navarro Cupuerán, Mónica Patricia (2016)
The present study pursues as a general objective to determine the feasibility for the implementation of a communal tourist service enterprise in the city of Santo Domingo de los Colorados, province of Santo Domingo de los Tsachilas, on which an strict and methodologic procedure has been followed to determine the investment feasibility. The selected methods have supplied significatively in the development of the investigation. The inductive method was applied during the observation and analysis of the tourists who visit Santo Domingo and the services that they prefer. This permitted the analysis of the demand and the adequate service determination for the goal part which the enterprise wants to supply. The deductive method was applied for explaining the feasibility of the project on interpreting the results of the market study, the income-outcome valuation and the results of the financial valuation. The analytic method was applied along the whole study of feasibility owing to no part of itself could be structured without a previous analysis, the most analysis intensity found center on the financial valuation for being the point that determinated the economic and financial viability, supplying to the investor enough information to decide to invest. The synthetic method was applied in the results interpretation of the work field and on making the conclusions and recommendations. The data collection technique that was used as the main way was the survey. National and foreign tourists were surveyed who visited the Tsáchilas communities of Santo Domingo. The market study reflected a growing demand for agro tourism. The potential demand of the company is 1 794, while the actual demand and effective demand is 1 023 and 724, respectively. The unsatisfied demand is conformed by 727 tourists who, according to market research, they would travel for a stay of two or three days, which represents a total of 1448 tour packages that could be sold. The growth rate of the tourism sector is 7%; and consumption or average per capita spending on tourism is $ 240.00 per year, figures that emerge from the same market research. To position the service in the market, advertising will take place, the message will be communicated through various means, but mainly the internet is considered as the most effective way to reach executive customers, entrepreneurs and households. After verifying the existence of unsatisfied demand we proceeded to the stage of organizational design. A constitutive memorandum was made, establishing itself as a company with limited liability. The following charges were initially considered: Manager, secretary-bookkeeper, executive marketing and public relations, sales and after-sales executive, concierge and outside legal counsel:. The structural organigram provides adequate classical structure (pyramid) to organize functions within the company. The third stage focused on the technical study in which it was determined that an initial construction of four cabins with two bedrooms each, offers a capacity of maximum lodging of 8 rooms x 360 nights a year = 2,880 would be the time that the rooms would be rented if they operated at 100% of the installed capacity. However in the first year, according to the sales forecast, the company will require only 50.27% of its installed to meet the unmet demand capacity. Office facilities will be rented at a strategic site within the city since the purchase of an office is a significant investment that is no priority over other investment needs. The cabins will be built on a farm in the rural parish of San Jacinto del Bua, belonging to the canton Santo Domingo. The initial investment is for $ 76,936.68 and it is distributed as follows: $ 69,077.40 in fixed assets, $ 3,785.25 in deferred tax assets, and $ 4,074.03 as working capital. The estimate of costs and revenues will allow financially evaluate the project and determine its profitability. For the first year of operation fixed costs increase to $ 61,531.22; $ 36.350,00 variable costs and total costs increase to $ 97,881.22. Incomes increase the sum of $ 116,320.00. With the obtained results, the company must sell the service at least 76.94% of the total budgeted agro tourist packages to be sold in the first year of operations; 55.16% in the fifth year and 38.68% in the tenth year. In addition, it is indicated that the minimum dollar amount that must be sold annually so that they can cover all costs and expenses and not to find losses although not find a profit in the first year is $ 90,377.10; for the fifth year is $ 102,226.86; and for the tenth year $ 128,360.18. The net present value (NPV) of the first year is $ 17 958,42; in the fifth year amounts to $ 30 674,07 and the tenth year is $ 32 140,54. The cost-benefit ratio gives a value of $ 1.50; which explains that for every dollar invested earnings of 50 cents will be obtained. The result is greater than 1, and in accordance with the rule, it is showed that the project is viable. Based on the discounted net flows, capital recovery period (PRI) would be 3 years, 2 months and 1 day. The internal rate of return of 45.49% would be. Whereas this result is greater than the rate of opportunity cost, it allows proving the feasibility for the implementation of the project. The sensitivity supports a decrease of 13.15% in revenue, or an increase of 18,52% in costs. This explains that the project will not be sensitive to this level of cost increase nor in the face of incomes decrease, enabling business profitability. The study presents as main conclusions that there is a needed demand to start agri-tourism activities in Santo Domingo, having determined the feasibility of the project and thus the recommendation to invest in the creation of tourist company NATURAL TOUR in the canton Santo Domingo, province of Santo Domingo de los Tsáchilas, since the financial evaluation demonstrates the possibility of achieving a net profit in the first year for $ 13 451,87 an uptrend and so achieve the tenth year $ 102 909,25.